2013
DOI: 10.1016/j.visres.2013.04.001
|View full text |Cite
|
Sign up to set email alerts
|

The Simon effect of spatial words in eye movements: Comparison of vertical and horizontal effects and of eye and finger responses

Abstract: Spatial stimulus location information impacts on saccades: Pro-saccades (saccades towards a stimulus location) are faster than anti-saccades (saccades away from the stimulus). This is true even when the spatial location is irrelevant for the choice of the correct response (Simon effect). The results are usually ascribed to spatial sensorimotor coupling. However, with finger responses Simon effects can be observed with irrelevant spatial word meaning, too. Here we tested whether a Simon effect of spatial word m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
19
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 49 publications
4
19
0
Order By: Relevance
“…Researchers suggested that the sensorimotor representation evoked by location words influences the motor response, eventually resulting in a semantic Simon effect (Khalid & Ansorge, 2013). The semantic Simon effect in Exper iment 4 is consistent with the embodied cognition view.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Researchers suggested that the sensorimotor representation evoked by location words influences the motor response, eventually resulting in a semantic Simon effect (Khalid & Ansorge, 2013). The semantic Simon effect in Exper iment 4 is consistent with the embodied cognition view.…”
Section: Discussionsupporting
confidence: 60%
“…The Simon effect refers to the fact that responses to compatible stimuli (i.e., the stimuli are ipsilateral to the response) are faster and more accurate than responses to incompatible stimuli (i.e., the stimuli are contralateral to the response), while stimulus location is irrel evant to the task. Recently, many studies have used location words (e.g., left or right) to produce the semantic Simon effect (Khalid & Ansorge, 2013;Pellicano, Lugli, Baroni, & Nicoletti, 2009). In the semantic Simon task, location words are presented at the center of a display, and participants are told to respond to a feature of the word, such as color, while ignoring its meaning.…”
mentioning
confidence: 99%
“…The ocular-motor theory of IOR emphasizes the correlation between IOR and oculomotor system: the peripheral cue produces an automatic activation of an eye movement to that location, which generates IOR (Rafal et al, 1989; Kingstone and Pratt, 1999; Klein, 2000). And, both spatial IOR and the Simon effect could be influenced by eye movements (Abrahamse and Van der Lubbe, 2008; Buetti and Kerzel, 2010; Khalid and Ansorge, 2013). In the present study, in order to minimize the effects of eye movements, we instructed the participants to fixate at the central box throughout the experiment.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, our results indicate that merely an activation of a part of space by a word makes the memorized object in the space more tangible, which is evident by eye curvatures. Thirdly, it appears that meaning-location compatibility (e.g., Khalid and Ansorge 2013) or the location-saccade direction compatibility (Theeuwes et al 2005) effects should not be generalized over all spatial directions but rather tested separately.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, previous research suggests that participants make faster saccades to the word sun, when located in the upper part of the screen compared to the lower part (Dudschig et al 2013). Moreover, it seems that even when irrelevant to the task, word meaning can influence the time of saccade initiation: Saccades were faster when their direction (left/ right, above/below) from the centrally presented word (left/ right, above/below) were compatible than when they were incompatible (Khalid and Ansorge 2013).…”
Section: Introductionmentioning
confidence: 97%